First person - Talia Nasr (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Talia Nasr is first author on 'Disruption of a Hedgehog-Foxf1-Rspo2 signaling axis leads to tracheomalacia and a loss of Sox9+ tracheal chondrocytes', published in DMM. Talia is a MD/PhD student at the University of Cincinnati, USA, currently in the final two MD years, with the PhD work completed in the lab of Aaron Zorn, investigating the pathogenesis of congenital tracheoesophageal defects.